Estrutura classificatória e análise cientométrica: estudo aplicado à produção científica de pesquisadores do Centro de Valorização Agroalimentar de Compostos Bioativos da Amazônia, no período de 2010-2013 - BORGES, Aline Santiago (Universidade Federal de Minas Gerais, 2017)
This research is about an analysis of the scientific production themes of the community of researchers associated with the Agri-food Value of Amazon Bioactive Compounds Center – Centro de Valorização Agroalimentar de Compostos Bioativos da Amazônia (CVACBA) – of the Guamá Science and Technology Park – Parque de Ciência e Tecnologia Guamá (PCT Guamá). The questions posed in this study were: Could enumerative classification, properly elaborated according to the prescriptions of the field of Library and Information Science, using input obtained from scientific production, contribute to an assessment of the research carried out by a given community of researchers? How could the themes of researchers’ scientific production be correlated to the themes presented as interest of their institution? The general objective of this research was to analyze, thematically, the scientific production of CVACBA researchers from 2010 to 2013, aiming at an assessment of the research carried out, by means of a methodology encompassing classificatory structures. The specific objectives were as follows: identify the themes studied by the researchers, create a classificatory structure of scientific production; identify the most recurrent and relevant themes; introduce and test the bibliometric (scientometric ) method of CVACBA scientific production from hierarchical classification; discuss the possibility of comparison between the themes addressed by the researchers and presented in the quantified classificatory structure, as well as the interest issues about CVACBA proposed and published by PCT Guamá. In its turn, the theoretic-methodological approach support addresses the bibliometrics / scientometrics and their bases, the scientific communication and production, technology transferring, as well as classification and its bases, involving knowledge representation and knowledge organization systems, subject analysis, semantics, and terminology. The present research is exploratory with quantitative and qualitative approaches; it is a case study. The empirical object of this study was the scientific production of the Center researchers. For such production analysis, 132 academic journal essays, published by researchers, from 2010 to 2013, were recovered via Lattes Curricula (Brazilian Government website). The identification and analysis of the 1,649 topics of those published articles were conducted via the following methods: subject analysis, construction of classificatory structure and scientometrics (thematic variable). The results allowed identifying Chemistry and Biology as the classes with major representativeness in that given realm, that is, the classes in which there are the topics mostly addressed by researchers. With regard to the comparison of the themes of the scientific production structures, alongside the Center profile, it was noted that the correlation found was significant, in general terms. In the Center thematic profile structure, the themes were presented in a quite brief way; whereas the researchers explored the thematic / conceptual universe in a far more extensive way, producing knowledge, which, despite corresponding to defined areas of interest, are at a higher detailed level. The research demonstrates the integration between classificatory structures and scientometrics, and, given that this approach might qualify scientific production thematic analyses, providing clarifying elements concerning the research developed. Major and minor recurring themes verification, throughout the research carried out, in a given period, allows the scientific community alongside other ones involved in science and technology to have access to the evidences of the theme approaches and their relevance to research development.